A novel displacement amplification factor (Cd) for steel moment-resisting frames based on performance. (December 2022) - Zahedi, Mohammad Javad; Saffari, Hamed
Highlights: A new displacement amplification factor formula (Cd) has been. Three sample structures were used to evaluate the suggested equation. The suggested Cd equation propsed for three IO, LS and CP performance levels of structure. The proposed Cd formula provides more reliable estimation in comparison to Eurocode8. Abstract: Displacement amplification factor is one of the most important factors in seismic design of structures. Choosing the sizes of structural section in steel moment resisting frames generally depends on the story drift limitation. In current regulations, the inelastic displacement is determined by multiplying obtained displacement out of equivalent linear static analysis by a displacement amplification factor (Cd ). In this paper, several moment resisting frames have been analyzed using elastic static and inelastic dynamic analyses. After post processing of the results, a relation has been suggested for displacement amplification factor which varies along the height of the frame in three different performance levels. Three sample structures illustrate that how proposed relation improves the Cd and makes more rational results than traditional Cd . Results also show that the considered displacement amplification factor in Eurocode8 makes lower approximation of displacement.